Interpersonal communications at core of conflicts' escalation in organization. The interplay of interpersonal communication escalation, people's habitus and psycho-sociological processes are more important than contextual factors. Issue 1 (1st January 2021) - Valitova, Aysylu; Besson, Dominique
Abstract : Purpose: Develop an integrated model to analyze conflicts at work and apply it to a case study. The core of the conceptual model is constituted by the interpersonal relationships modalities using the Palo Alto school theorization (symmetrical and complementary relations framework in people's relative positioning). This model also articulates inside this interpersonal relationships structure five other dimensions: Perception processes, Life dynamics, Habitus from Bourdieu and developed by Lahire, psychosociological processes and sociological factors (including cultural ones). We apply this model to the case study of a Community center in a French city where a serious conflict happens with the final consequence of the closure of the center. Design/methodology/approach: In-depth case study by long conversations (more than interviews) with the main protagonists of the Community center and of the conflict. These talks have been completed by secondary sources and extended review of newspaper articles. Findings: Our model revels to be pertinent to enlighten the multiple dimensions of the conflict. In particular, we show that the dynamics of interpersonal relationships is central in the conflict development and is embedded in multiple psychosociological processes (perceptions processes with deep perceptive divergences between people, personal construction of Social Identity by protagonists, group thinking, active minority construction, etc.). The sociological factors, as well of personal habitus, have an effect but are not determinants of people's behavior. People are partially conscious of the occurring phenomena but cannot be considered as omniscient, purely strategic actors. Research limitations/implications: 1-Application of the conceptual model is applied only on one case study. 2-More attention should be given to prospective dimension of stories and storying (antenarrative). Practical implications: The case analysis based on our reactional model of conflicts leads to point out several mistakes in the management of the considered organization and more precisely in the management of the conflictual relationships. Change of level 2 has been misconducted by the top manager of the Community center and we show which alternative decisions could have been made in order to avoid the burst of the conflict. More general conflict management methods can be deduced from our analysis. Originality/value: Articulation of these different concepts in an integrated model has never been previously made neither applied in a case study.